Analisis Hubungan Clinical Autonomy Terhadap Kepuasan Kerja Dokter Spesialis Obstetri dan Ginekologi Dalam Tindakan Seksio Sesarea Pada Sistem Jaminan Kesehatan Nasional - Mappaware, Nasrudin Andi; Emilia, Ova; Hadijono, Soerjo; Malinta, Umar; Hakimi, Mohammad; Soetrisno, Soetrisno; Tiro, Eddy (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2019)
Background: In Indonesia, the National Health Insurance System (NHIS) is an implementation of law No. 40 of 2004 on the National Social Insurance System in health sector with universal health coverage (UHC) concept. Therefore, the satisfaction of specialist’s work will be very influence towards hospital works. The previous research (Nasruddin, 2017) about factor analysis related to job satisfaction of doctor specialist for obstetrics and gynecology (SpOG) toward Sectio Caesarea (SC) on NHI showed that medical service (transparency and remuneration) and working condition have significant correlation towards work satisfaction of doctor SpOG in SC on NHI. Objective: to analyze the correlation of clinical autonomy on job satisfaction of doctor SpOG on Sectio Caesarea on National Health Insurance system.Method: A quantitative research by applying analytic observational study with cross sectional design.Materials and Research: This research was conducted in Makassar. A number of sample was 73 doctors SpOG. Data was obtained by clinical autonomy questionnaire having been tested its validity and reliability. The result of the research was analyzed by using chi-square test. Result: Based on the correlation of characteristics towards work satisfaction of doctor SpOG in SC on National Health Insurance system found that age category between 36 – 45 years old is satisfied, female is satisfied, working duration more than 5 years is dissatisfied and public hospital status is dissatisfied. There is no correlation between clinical autonomy in this case is control overwork (p = 0.170) and prerogative obtain need service (p = 0.240) on job satisfaction of doctor SpOG in Sectio Caesarea on National Health Insurance System.Conclusion: There is no relation between clinical autonomy on job satisfaction of doctor SpOG in Sectio Caesarea on National Health Insurance System. Even though the doctors SpOG are not satisfied with NHI (medical service and working condition) but the doctors are able to work professionally with clinical autonomy. Keywords: clinical autonomy, doctor SpOG, National Health Insurance System